Migration Determinants at a Local Level - Josep-Maria Arauzo-Carod; Daniel Liviano-Solís (European Regional Science Association (ERSA), 2012)
This paper is about determinants of migration at a local level. We use data from Catalan municipalities in order to understand what explains migration patterns of population between 2004 and 2010. The contribution of this paper is to present an empirical application made using data from municipalities in Catalonia between 2004 and 2010. This is a period in which economic activity increases considerably, with the exception of the period 2008-2010, characterised by the start of the economic crisis. The growth in terms of GDP and workforce attracted a lot of international migrants due to a growing demand of low-skilled jobs. At the same time, house prices rose considerably at the main urban areas, a situation that pushed young educated couples from the centre of these areas to the surrounding (cheaper) municipalities, in a typical example of counterurbanization, where migrations movements are from urban to rural areas. Given the characteristics and typologies of Catalan migration movements, in this paper we will focus at intra-regional migrations, which are of considerable importance during the period analysed here. Our results show the importance of counterurbanization and suggest that migration determinants do not affect all types of municipalities in the same way.
Keywords: 330